2017
DOI: 10.1007/s00359-017-1231-3
|View full text |Cite
|
Sign up to set email alerts
|

From electromyographic activity to frequency modulation in zebra finch song

Abstract: Behavior emerges from the interaction between the nervous system and peripheral devices. In the case of birdsong production, a delicate and fast control of several muscles is required to control the configuration of the syrinx (the avian vocal organ) and the respiratory system. In particular, the syringealis ventralis muscle is involved in the control of the tension of the vibrating labia and thus affects the frequency modulation of the sound. Nevertheless, the translation of the instructions (which are electr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…In fact, it has been shown that from EMGs measurements in the vS muscle, it is possible to estimate the frequency modulations of zebra finch song. This requires transducing EMGs into muscle force by means of a model for the muscle, and this force into labial tension ( Doppler et al, 2018 ). In order to build this bridge between EMG and frequency modulation several quantitative tools had to be developed.…”
Section: From Syringeal Muscle Activity To Soundmentioning
confidence: 99%
See 3 more Smart Citations
“…In fact, it has been shown that from EMGs measurements in the vS muscle, it is possible to estimate the frequency modulations of zebra finch song. This requires transducing EMGs into muscle force by means of a model for the muscle, and this force into labial tension ( Doppler et al, 2018 ). In order to build this bridge between EMG and frequency modulation several quantitative tools had to be developed.…”
Section: From Syringeal Muscle Activity To Soundmentioning
confidence: 99%
“…In this way, as the electrical activity shortens the slack, the difference between the muscles actual length and the slack is transduced into force ( Shapiro and Kenyon, 2000 ) through a nonlinear (exponential) function. These models were developed and implemented in Doppler et al (2018) . Figure 7 shows the spectrogram of a song, and the temporal evolution of the estimated fundamental frequency after integrating the muscle model and the labial model with the syringeal EMG as input (shown in blue in Figure 7A ).…”
Section: From Syringeal Muscle Activity To Soundmentioning
confidence: 99%
See 2 more Smart Citations
“…An important example is the activation of the song production circuitry during sleep in oscine songbirds. In the best-studied species, the zebra finch (Taeniopygia guttata), song in adult males is highly stereotyped and consists of 4-8 different syllables, each of which is accompanied by distinct activation patterns of the muscles of the vocal organ, the syrinx [16][17][18][19]. Song-like activation during sleep involves contractions of the syringeal muscles without concurrent activation of the © 2021 The Author(s) Published by the Royal Society.…”
Section: Introductionmentioning
confidence: 99%